Growth differentiation factor 15 as a potential diagnostic biomarker for rheumatoid arthritis: a systematic review - Xu Liu; Anko E. Essien; Wenhao Lu; Hongfu Jin; Linyuan Pan; Yusheng Li; Wenfeng Xiao (Bone & Joint Research)
Aims: This systematic review aimed to investigate the association between growth differentiation factor 15 (GDF-15) and rheumatoid arthritis (RA) disease activity, explore the differences at the genetic level, and evaluate the value of GDF-15 in diagnosing RA. Methods: A comprehensive literature search was conducted using PubMed, Web of Science, Cochrane Library, and Embase on 23 August 2023. Methodological quality was independently assessed by using the Agency for Healthcare Research and Quality scale. The primary parameters analyzed were the serum GDF-15 concentration, disease activity, and diagnostic sensitivity and specificity. Results: A total of 469 documents were retrieved, and five clinical studies were ultimately included. In the included studies, GDF-15 serum levels were found to be notably greater in RA patients than in healthy individuals, and these levels exhibited a positive correlation with disease severity. Furthermore, increased GDF-15 serum levels were associated with specific gene variations in RA patients, but varied according to ethnicity. In two included studies, GDF-15 showed high diagnostic sensitivity and specificity for highly active RA, demonstrating its utility as a diagnostic biomarker of RA. Conclusion: GDF-15 expression is increased in RA patients and is associated with disease activity; thus, GDF-15 is potentially an effective diagnostic biomarker for RA. However, additional high-quality studies, especially randomized controlled trials and cohort studies with follow-up data, are needed to assess the role of GDF-15 in RA. Cite this article: Bone Joint Res 2025;14(5):389–397.